2006
DOI: 10.1111/j.1474-9726.2006.00198.x
|View full text |Cite
|
Sign up to set email alerts
|

Free radical generation by skeletal muscle of adult and old mice: effect of contractile activity

Abstract: SummaryOxidative modification of cellular components may contribute to tissue dysfunction during aging. In skeletal muscle, contractile activity increases the generation of reactive oxygen and nitrogen species (ROS). The question of whether contraction-induced ROS generation is further increased in skeletal muscle of the elderly is important since this influences recommendations on their exercise participation. Three different approaches were used to examine whether aging influences contraction-induced ROS gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
190
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(206 citation statements)
references
References 47 publications
15
190
1
Order By: Relevance
“…Consistent with a role of mitochondria as a contributor to age‐related muscle redox changes, reports have shown that isolated213, 236 and intact mitochondria21 in skeletal muscle fibres exhibit an age‐dependent increase in H 2 O 2 generation. Considerable evidence has shown that age‐related mitochondrial oxidative damage can alter mitochondrial integrity and function in ageing skeletal muscle.…”
Section: Non‐enzymatic Key Antioxidants That Contribute To the Maintementioning
confidence: 54%
“…Consistent with a role of mitochondria as a contributor to age‐related muscle redox changes, reports have shown that isolated213, 236 and intact mitochondria21 in skeletal muscle fibres exhibit an age‐dependent increase in H 2 O 2 generation. Considerable evidence has shown that age‐related mitochondrial oxidative damage can alter mitochondrial integrity and function in ageing skeletal muscle.…”
Section: Non‐enzymatic Key Antioxidants That Contribute To the Maintementioning
confidence: 54%
“…The automated glutathione recycling assay described by Anderson (2002), modified for use on a 96-well plate reader (Benchmark, Biorad, UK), was used to measure total and oxidised gastrocnemius glutathione content as described previously (Vasilaki et al 2006). Protein thiol and malonaldehyde contents of the muscle were measured as previously described (Di Monte et al 1984).…”
Section: Measurement Of Muscle Mass and Calculation Of Csamentioning
confidence: 99%
“…The total glutathione concentration in liver was measured according to Anderson (1996) along with modification for use with a 96‐well plate reader (Vasilaki et al., 2006) and expressed in nmol per mg protein. In both analyses, protein content was measured with the Lowry method with Peterson modification (Lowry et al., 1951; Peterson, 1977).…”
Section: Methodsmentioning
confidence: 99%